LOGICO-SEMANTIC RELATION IN NEWSPAPER TEXTS ON JAKARTA TERROR ATTACK - Annisa Risma Khairani Lubis; Masdiana Lubis (Proceedings of ISELT FBS Universitas Negeri Padang, 2018)
This research aimed to describe the type of logico-semantic relation and to explain how logico-semantic relation are used in newspaper texts on Jakarta terror attack. The data are clause complexes in Islamic State militants claim deadly attack in Jakarta’s The Jakarta Post (Text A), IS-linked group suspected of carrying out Jakarta attacks: police’s The New Straits Times (Text B) and ISIS behind deadly Jakarta attack’s The Straits Times (Text C) articles. As the result, both parataxis and hypotaxis are obtained.  In terms of logico-semantics relations, it is found that nine of ten types of logico-semantic relations are used in Text A and eight types of logico-semantic relations are used in Text B and Text C. The types that were not found in three newspaper texts are paratactic elaboration and paratactic idea. The logico-semantic relation type which dominantly occurs in three newspaper texts are paratactic extension in Text A, hypotactic locution in Text B and hypotactic elaboration in Text C.